Energy transfer between Eu3+ and Nd3+ in near-infrared emitting β-triketonate coordination polymers - Abad Galán, L.; Sobolev, A.; Skelton, B.; Zysman-Colman, E.; Ogden, Mark; Massi, Massimiliano (R S C Publications, 2018)
© The Royal Society of Chemistry. Isomorphous ß-triketonate-based lanthanoid polymers containing tris(4-methylbenzoyl)methanide (mtbm) and Rb+ with formula {[Ln(Rb)(mtbm)4]2}n (Ln = Eu3+ and Nd3+) have been synthesised and structurally characterised. The photophysical properties for the Nd3+ complex presented relatively long lifetimes and high quantum yields in comparison with analogous ß-diketonate complexes. Mixed lanthanoid complexes were also formed and their luminescence properties studied, with effective sensitisation of the 4F3/2 of Nd3+via the 5D0 of Eu3+, which is to the best of our knowledge the first example of Eu3+ to Nd3+ sensitisation in a structurally defined coordination complex or polymer.